Kikuchi-Fujimoto disease: a rare cause of cervical Adenopathies - Pina, Rui; Fonseca, Isabel; Saldanha, Maria Helena (Portuguese Journal Internal Medicine, 2004)
Kikuchi-Fujimoto disease, also nominated histiocytic necrotizing lymphadenitis, was described in 1972 and is characterised by a benign, self-limiting course and unknown aetiology affecting predominantly young women in their second or third decades of life. Clinical features include bilateral cervical lymphadenopathy in association with fever, even though other constitutional symptoms may be present. Diagnosis is based on histopathological findings, being important to consider differential diagnosis with infectious, autoimmune and lymphoproliferative lymphadenopathies. This disease has a good prognosis without therapy, nevertheless, if necessary, nonsteroid anti-inflamatory drugs (NSAID’s) or low dose corticosteroids are used. The authors present a case of a 26 years old woman with cervical bilateral lymphadenopathies and malaise. The histological result of an excised lymph node was histiocytic necrotizing lymphadenitis. Evolution was excellent and the patient was assymptomatic without any treatment.